Factors influencing student satisfaction towards distance learning Apps during the Coronavirus (Covid-19) pandemic in Malaysia - Karim, Md Wasiul; Haque, Ahasanul; Ulfy, Mohammad Arije; Hossin, Md Suliman (Human Resource Management Academic Research Society, 2021)
The latest coronavirus epidemic has witnessed a catastrophic fall in traditional education system and a significant change to app-based learning to maintain learning continuity. The conventional face-to-face teaching approach has been drastically altered with the addition of a new dimension in which student satisfaction is paramount. This current research paradigm is based on the TAM model. Students residing in Klang Valley, Malaysia, obtained a total of 483 data. By deploying SPSS and AMOS version 24.0, the study found self-efficacy as one of the deciding factors of student satisfaction; there is a strong correlation between self-efficacy and satisfaction. Furthermore, perceived usefulness and perceived ease of use are also influenced by self-efficacy. In contrast, perceived ease of use does not affect perceived usefulness, and perceived usefulness does not affect satisfaction. Finally, to increase the level of distance learning during COVID-19 outbreak, recommendations are made to enhance the virtual learning environment.